Afterload reduction after non-invasive vagus nerve stimulation in acute heart failure - Nagai, Michiaki; Dote, Keigo; Kato, Masaya; Sasaki, Shota; Oda, Noboru; Förster, Carola Y. (Frontiers in Human Neuroscience, 2023)
Introduction: While central blood pressure (BP) has been recognized as a major indicator of left ventricular (LV) afterload, the reduction of central pressure decreases LV afterload and may prevent heart failure (HF) decompensation. Non-invasive transcutaneous vagus nerve stimulation (tVNS) has been reported to improve cardiac function in HF patients. In this study, we investigated the relationship between active tVNS and reduction of central BP in patients with acute HF (AHF). Methods: The 22 patients hospitalized for AHF after initial stabilization (median 80 yrs, males 60%) were randomly assigned to active or sham group, and low-level transcutaneous electrical stimulation (LLTS) (20Hz, 1mA) was delivered using an ear clip attached to the tragus (active group) or the earlobe (sham control group) for 1hour daily over 5 days. Central aortic systolic pressure (CASP), brachial systolic BP (SBP), diastolic BP (DBP) and heart rate (HR) were noninvasively measured before and after stimulation. Results: Baseline characteristics were not significantly different between active and sham groups. In the active group, each of CASP, SBP, DBP and HR was significantly decreased after stimulation (all p<0.05), while each of CASP, SBP, DBP and HR was significantly increased after stimulation in the sham group (all p<0.05). All the changes in CASP, SBP, DBP and HR before and after stimulation were also significantly different between active and sham groups (all p<0.01). No device-related side effects were observed. Conclusion: In this study, the left tragus tVNS resulted in an acute afterload reduction in the elderly AHF patients. Non-invasive LLTS may be useful and safe for reducing afterload in AHF.